Seeing Fingers The Story of Louis Braille - DeGering, Etta (New York David McKay Company, Inc, 1962)
Blind since childhood, Braille developed his system to help the blind read in his teens, gained its acceptance and taught the blind.
Keywords: Braille, Louis -- 1809-1852; Physically Handicapped; Frontier & Pioneer Life -- Juvenile Literature